2016
DOI: 10.1007/s00339-016-0221-6
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on the magnetic property and ferroelectricity in hexaferrite SrFe12O19

Abstract: We studied the temperature effect on magnetic and electrical properties in bulk SrFe 12 O 19 prepared by conventional ceramic technique. The jumping behavior of magnetization has been observed under the zero-fieldcooling mode, but disappeared under the field-cooled cooling mode. The spin moment of iron ions reorients below 50 K leading to the magnetic structure changes. Magnetic parameters, saturation magnetization (Ms) and coercivity field (Hc), show opposite tendency with temperature throughout the measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…In addition, the magnetization during FCC measurement was increased by lowering the temperature for all studied samples except for a slight saltation for SFO and SGFCO-1 samples. The same type of behaviour was observed for the SrFe 12 O 19 samples by Gang Qiang 67 for the 50 Oe applied field. The primary distinction between ZFC and FCC is whether an external magnetic field is dominating throughout the cooling process.…”
Section: Resultssupporting
confidence: 78%
“…In addition, the magnetization during FCC measurement was increased by lowering the temperature for all studied samples except for a slight saltation for SFO and SGFCO-1 samples. The same type of behaviour was observed for the SrFe 12 O 19 samples by Gang Qiang 67 for the 50 Oe applied field. The primary distinction between ZFC and FCC is whether an external magnetic field is dominating throughout the cooling process.…”
Section: Resultssupporting
confidence: 78%
“…The magnetoelectric coupling is taken to be linear because the ferroelectric critical temperature is much smaller than the ferromagnetic one [21,22]:…”
Section: The Modelmentioning
confidence: 99%
“…Significant discoveries have unveiled the remarkable coexistence of large ferroelectricity and robust ferromagnetism within SFO, with the ferroelectric critical temperature notably smaller than the ferromagnetic counterpart [21,22]. Moreover, investigations have revealed that BaFe 12 O 19 (BFO) and PbFe 12 O 19 (PFO) also exhibit ferroelectric (FE) properties.…”
Section: Introductionmentioning
confidence: 99%
“…M‐type hexaferrite is a traditional permanent magnet with high saturation magnetization and large magnetic coercivity . The ferroelectricity of M‐type hexaferrites has been verified by classic polarization hysteresis loops with good saturation, huge abnormal change in dielectric constants near Curie temperature for ferroelectric phase transition and two nonlinear I–V peaks for switching of polarization field or domains . However, the magnetoelectric coupling effect in pure SrFe 12 O 19 is pretty weak.…”
Section: Introductionmentioning
confidence: 99%